PLAU accelerates extracellular matrix remodeling through partial epithelial-mesenchymal transition in head and neck squamous cell carcinoma - Liu, Zhichang; Jia, Qiaojing; Yang, Zhichao; Zhang, Haizhong; Wang, Jingmiao; Liu, Lisha; Lou, Dan; Wang, Jianxing (Translational Cancer Research, 2026)
Background: Head and neck squamous cell carcinoma (HNSCC) poses a significant global health challenge, accounting for approximately 4.5% of all malignancies, with approximately 890,000 new cases and 450,000 related deaths annually. Research indicates that partial epithelial-mesenchymal transition (p-EMT) figures prominently in the progression and metastasis of HNSCC. This study was conducted to determine whether the differentially expressed genes (DEGs) in HNSCC are key regulators of p-EMT.Methods: Twelve DEGs were screened out from the Gene Expression Omnibus, and the clinical characteristics were obtained from The Cancer Genome Atlas. Subsequently, PLAU was confirmed as a gene related to p-EMT. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses were applied to predict the potential functions of PLAU. Subsequently, immunohistochemistry was performed to examine the expression of PLAU and p-EMT markers in 75 samples of HNSCC tissue. To clarify the relationship between PLAU and p-EMT, PLAU was knocked down with small interfering RNA (siRNA), and wound healing, Transwell, and Western blot assays were conducted.Results: The results of univariate and multivariate Cox regression analyses based on microarray data indicated that PLAU is involved in HNSCC. Consistent with this, PLAU expression was strongly correlated with p-EMT marker expression, and inducible knockdown of PLAU in HNSCC cell lines inhibited cell proliferation, cell invasion, and migration. Moreover, the PLAU-knockdown group had significantly higher and lower ITGA5 and PDPN expression, respectively.Conclusions: These findings confirm PLAU to be an independent predictor of prognosis in HNSCC and involved in p-EMT-related metastasis.